Methyl phenlactonoates are efficient strigolactone analogs with simple structure - Jamil, Muhammad (J Exp Bot, 2018)
Strigolactones (SLs) are a new class of phytohormones that also act as germination stimulants for root parasitic plants, such as Striga spp., and as branching factors for symbiotic arbuscular mycorrhizal fungi. Sources for natural SLs are very limited. Hence, efficient and simple SL analogs are needed for elucidating SL-related biological processes as well as for agricultural applications. Based on the structure of the non-canonical SL methyl carlactonoate, we developed a new, easy to synthesize series of analogs, termed methyl phenlactonoates (MPs), evaluated their efficacy in exerting different SL functions, and determined their affinity for SL receptors from rice and Striga hermonthica. Most of the MPs showed considerable activity in regulating plant architecture, triggering leaf senescence, and inducing parasitic seed germination. Moreover, some MPs outperformed GR24, a widely used SL analog with a complex structure, in exerting particular SL functions, such as modulating Arabidopsis roots architecture and inhibiting rice tillering. Thus, MPs will help in elucidating the functions of SLs and are promising candidates for agricultural applications. Moreover, MPs demonstrate that slight structural modifications clearly impact the efficiency in exerting particular SL functions, indicating that structural diversity of natural SLs may mirror a functional specificity.